Complex Sentences Tense Agreement in Kurdish - Khalid, Trifa Omar; Aziz, Aryan Sdiq; Gharib, Nali Adham; Hama Amin, Tanya Ismail; Aziz, Salm Hassan; Hama Gharib, Bahra Salam; Hama Saeed, Rasti Ayub (Journal of Linguistics and Social Sciences, 2023)
The information inside sentences is conveyed from different perspectives. Tense, which becomes the primary source of information in sentences, is the different categories of verb inflection (Mahwi & Aziz,2018). Sentence structures are the various and also specific components of the speakers' intended Syntax and Semantics situations (Gharib & Ismail, 2019). The information of time inside a simple sentence concerns the contents of time of a single verb. On the other hand, complex sentences require two sources of information about the tense of the verbs. Tense agreement in sentences depends on the structure and elements inside complex sentences. Thus, all of the (complex sentences, tense, tense agreement) will be the analysis source in this research paper. For this purpose, special attention is given to each of the three mentioned ones, and the nature of their sequences in the language is analyzed with examples in the Kurdish language.